The Impact of Child Protection Training on Nurses' Self-Efficacy in Detection and Reporting of Child Abuse in Saudi Arabia - Almutairi, Albandari Lafi (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2024)
The World Health Organisation (WHO) has reported that child abuse and neglect constitute major international health problems that cause unacceptable morbidity and mortality. These forms of maltreatment can have severe physical and psychological effects on children’s development that persist into adulthood. Early detection of abuse and removing children from potentially hazardous and perilous conditions pose significant challenges. Nurses who care for children and families are uniquely positioned to identify children at risk of abuse and neglect during visits and have the opportunity to initiate interventions to prevent future harm. However, barriers such as a lack of experience, training, and confidence in handling abuse cases exist. Several training programmes have been developed to enhance nurses’ abilities to recognise and report child abuse. Studies demonstrate that these training programmes effectively improve nurses’ awareness, detection, and reporting of child abuse and neglect. In Saudi Arabia, The National Family Safety Program provides non-mandatory training to healthcare practitioners to support them in identifying and reporting child abuse cases through the Child Protection Multidisciplinary Training Programme (CPMTP) in multiple healthcare sites. The concept of self-efficacy has been used to assess the outcomes of clinical training programmes in other fields, as positive effects on self-efficacy should translate to desirable practice patterns. To date, few studies have explored the impact of child abuse training on nurses’ self-efficacy in recognising and responding to known and suspected cases of child abuse and neglect. Furthermore, none of these studies have been conducted in Saudi Arabia
APPROVED
Keywords: Child; Child abuse and neglect; Self-efficacy; Nursing; Training